MANAJEMEN SISTEM PENJAMINAN MUTU INTERNAL PERGURUAN TINGGI DALAM MENINGKATKAN MUTU LULUSAN - Muhammad Sularno; Iim Wasliman; Hendi Suhendraya Muchtar; Waska Warta (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The problem of this research is that graduates are not in accordance with the needs of the world of work. The results of the research are (1) Graduate quality management planning consists of indicators of Vision and mission, Objectives, Program, Time line, Monev plan, Follow-up has been well planned (2) Implementation of internal quality management consists of indicators of preparation, direction, program implementation, problems encountered, problem solutions, and implementation results have been properly arranged. (3) Evaluation of internal quality management consists of indicators of evaluation objectives, evaluation tools, evaluation results, and evaluation follow-up plans that have been carried out in accordance with applicable criteria (4) Internal quality management control consists of indicators of control objectives, types of controls, and results of controls has been carried out in accordance with approved operational standards. (5) Improvement of internal quality management consisting of indicators of development planning, development organization, development implementation, and development evaluation has been improved in accordance with suggestions and recommendations on the results of control measures (6) Internal quality management issues consist of indicators of planning, implementation, evaluation, control problems , and the upgrade is still there but it can be solved with a proper workaround. (7) Solutions to internal quality management problems consisting of indicators of planning, implementation, evaluation, control and improvement problems can be provided with a good solution. (8) The quality of student graduates, including academic and non-academic achievement indicators, has been well achieved